Val66Met polymorphism is associated with decreased likelihood for pediatric headache and migraine. (2nd September 2021) - Koute, Vasiliki; Michalopoulou, Amalia; Siokas, Vasileios; Aloizou, Athina-Maria; Rikos, Dimitrios; Bogdanos, Dimitrios P.; Kontopoulos, Eleftherios; Grivea, Ioanna N.; Syrogiannopoulos, George A.; Papadimitriou, Alexandros; Hadjigeorgiou, Georgios M.; Dardiotis, Efthimios
ABSTRACT: Background : Migraine is a complex multifactorial disorder and its pathogenesis still remains unclear. Evidence suggests the involvement of the activated trigeminovascular pathway, in which BDNF seems to play an important role. Therefore, BDNF polymorphisms are promising candidate susceptibility factors. Aim: BDNF rs6265 functional polymorphism was analyzed in order to determine its possible association with pediatric headache and migraine risk. Methods: The research included 120 consecutive pediatric patients who were diagnosed with headache and 120 healthy controls. The diagnosis was in compliance with the International Classification of Headache Disorders. Blood samples were collected from all participants and genotyped for rs6265. Results: BDNF rs6265 was significantly associated with decreased headache risk, particularly in the dominant model [Odds Ratio, OR (95% confidence interval, C.I.): 0.47 (0.26–0.85), p = 0.011] and the log-additive model [OR (95% C.I.): 0.48 (0.28–0.82), p = 0.0053]. During the sensitivity analysis, the associations were also maintained among patients with migraine. Conclusions: This is the first study to reveal a significant association of this BDNF variant with headache risk. Additionally, Val66Met was also for the first time related to decreased childhood migraine risk.